Research Trends in Career Interventions in Schools Based on Scopus from 1988-2022 - Muhammad, Rifqi (JURNAL KONSELING GUSJIGANG, 2023)
This research is motivated by the absence of researchers examining career interventions in schools. The purpose of this study is to describe the evaluation of career intervention research in schools from 1988-2022. This study uses a type of content analysis. Manuscripts analyzed n = 33, all indexed by Scopus. The results of the content analysis showed, namely: 1) empirical research on career interventions in schools fluctuated from 1988 to 2022. The highest was in 2022 and 2021, namely n = 6 (18%); 2) the type of manuscript is dominated by, namely articles n = 30 (91%); 3) research design and methods used are dominated by quantitative n = 22 (67%); 4) the content of the career intervention area in schools is dominated by classroom/school interventions n = 16 (49%); 5) Journal publishers are dominated by Journal of Career Development n = 4. Further researchers can examine the field of online career intervention which is still little studied by researchers. In addition, it is recommended for future researchers to use a qualitative design to examine online career interventions.